Some Brief Reflections on Values Training and Family Therapy Education - Childs, Brian H. (The Journal of pastoral care, 1987)
Notes that pastoral counseling frequently has been criticized for its unreflective use of secular psychology and psychotherapeutic theory but that general systems theory as applied to marriage and family counseling usually escapes this criticism. Argues, however, that a feminist critique counters this general assumption, particularly as it challenges systems neutrality regarding ethics and values. Proposes that it is essential for pastoral counselors to be educated in ethics and value analysis in order to deal authentically with issues encountered in marriage and family counseling.